Molecular engineering of organic semiconductors enables noble metal-comparable SERS enhancement and sensitivity - Gokhan Demirel (Nature Portfolio, 2019)
Organic semiconductors are considered promising Surface Enhanced Raman Spectroscopy platforms. Here the authors demonstrate that metal-free films based on a π-conjugated molecule containing a fully π-conjugated backbone provides an enhancement factor of 105 and detection limit of 10−9 M for methylene blue.